Resident Education Using a Novel, Low-Cost Postpartum Hemorrhage Simulator With Quantifiable Blood Loss. (October 2016) - Porter, Blake; Levy, Deborah; Mundy, David; Babbar, Shilpa; Williams, Karen; Maulik, Dev
Abstract : BACKGROUND: Postpartum hemorrhage is a common and potentially life threatening obstetrical emergency that has shown to be amenable to simulation. METHODS: Fourth year OB/GYN residents participated in a standardized simulation scenario of management of a PPH, prior to and after an educational intervention. The scenario used a novel simulator that quantifies blood loss and was built from low-cost, readily available materials. Residents then underwent an educational debriefing including instruction on PPH management and quantified feedback from their performance during the pretest simulation. Two months later, residents underwent posttesting using a similar PPH simulation. Statistical analysis used paired t test with P -value of less than .05 considered significant. RESULTS: Seven residents completed the pilot study. After the educational debriefing, residents performed corrective interventions earlier in the hemorrhage scenario. The primary outcome, total blood loss at the time of decision to perform exploratory laparotomy, significantly decreased 23% from 2, 271 mL on pretest as compared to 1, 743 mL on posttest simulation ( P =.03). The residents' ability to accurately estimate blood loss improved, however this trend did not reach statistical significance ( P =.15). DISCUSSION: Simulation training using this novel, low-cost PPH simulator allows for blood loss at the time of interventions to be accurately recorded and used in educational debriefings. Debriefing using management guidelines and quantified information on resident performance improved resident performance on follow up testing at 2 months.